Immediate Breast Reconstruction with a Deep Inferior Epigastric Perforator Flap in the Lithotomy Position. Issue 12 (December 2019) - Tamura, Shihoko; Satake, Toshihiko; Muto, Mayu; Shibuya, Mai; Narui, Kazutaka; Kobayashi, Shinji; Ishikawa, Takashi; Maegawa, Jiro
Abstract : Summary: Mastectomy and flap harvesting can be accomplished simultaneously in immediate deep inferior epigastric perforator (DIEP) flap breast reconstruction. However, this is not always possible, particularly in a teaching institution, where supervisors, trainees, and assistants must participate in the surgery, because there is not enough working space for breast and plastic surgeons to perform surgery together. We attempted to overcome this problem by placing the patient in the lithotomy position and have reported the outcomes. We evaluated patients who underwent unilateral immediate DIEP flap breast reconstruction in the supine or lithotomy position between October 2014 and July 2016. The surgeries were performed by the same inexperienced plastic surgeon in our hospital. In the lithotomy position, 1 plastic surgeon stands between the patient's legs and 1 stands beside the abdomen, and they perform DIEP flap harvesting simultaneously with mastectomy performed by 3 breast surgeons. After mastectomy, breast reconstruction is performed by 4 plastic surgeons. The supine position was used in the first 8 patients, and the lithotomy position was used in the following 8 patients. The mean operative time was 11 hours 21 minutes in the supine group and 8 hours 52 minutes in the lithotomy group, with a significant difference ( P = 0.027). Breast reconstruction with a DIEP flap in the lithotomy position is useful for teaching institutions because it provides sufficient working space and allows simultaneous procedures without prolonging operative time. However, issues such as pressure sores, nerve palsy, and difficulty in patient placement still exist. Abstract : Supplemental Digital Content is available in the text.